Plant growth regulators as thinners in guava orchards increase larger fruits with higher nutritional value - Silva, Marcelo de Souza; Leonel, Sarita [UNESP]; Leonel, Magali [UNESP]; Souza, Jackson Mirellys Azevedo; Ferreira, Rafael Bibiano [UNESP]; Martins, Rafaelly Calsavara [UNESP] (My University, 2022)
The production of large guavas guarantees better market prices. Chemical thinning is a practice performed to increase fruit size and nutritional value with benefits for growers and consumers. By using ethephon and benzyladenine at 0, 150, 300 and 450 mg L-1, fruit thinning in red guava was evaluated. The percentage of fruit setting and increase in fruit mass, marketable yield, soluble solids (SS), titratable acidity (TA), SS/TA ratio, pH, sugars, ascorbic acid, antioxidant activity, total phenolic compounds, flavonoids and pigments were evaluated. The plant growth regulators improved the setting of larger fruits. Fruit thinning higher efficiency was observed in the ethefhon and benzyladenine concentrations from 300 mg L-1 and upwards, however, benzyladenine induced phytotoxicity at the same concentrations. The chemical thinning can be used to promote larger fruits with better uniformity favoring higher marketability and as a source of interest compounds enhancing nutritional guava fruits value depending on the thinner and the concentration.
Keywords: Bioactive compounds; Cytokinin; Ethylene; Psidium guajava l.; Thinners